Hakka culture brand image design based on the human–computer interaction model - Chen, Rui (Frontiers in Psychology, 2022)
In order to better disseminate Hakka culture, this thesis focuses on the cultural dissection of Hakka culture in Gannan and the development and reflection of Hakka culture in Gannan. This paper aims to design the brand image of Hakka culture through human-computer interaction model. And based on this, this paper discusses the brand concept and the elements of cultural and creative products, and discusses the connection between Hakka cultural and creative and tourism brands. At the same time, this paper conducts an in-depth study on the creative design of the Hakka cultural tourism brand in Gannan. First of all, this article starts from the brand connotation, and analyzes the connotation and constituent elements of brand cultural and creative products. Secondly, this paper analyzes the relationship between Hakka culture and tourism brand cultural and creative product design. It discusses how to inherit and develop Hakka culture from the perspective of how Hakka culture is integrated into brand cultural and creative products. Thirdly, the design practice of cultural and creative products of the Hakka cultural tourism brand in Gannan. This paper first analyzes the visual image design of the cultural and creative products of the Hakka cultural tourism brand in Gannan. Then it analyzes the design of a series of cultural and creative products for the Hakka cultural tourism brand in Gannan. The experimental results show that the popularity of different products is more than 50%, which shows the effectiveness of this design.